2010
DOI: 10.1152/physiolgenomics.00006.2010
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in hypothalamus, liver, and adipose tissues and food intake response to melanocortin-4 receptor agonist in pigs expressing melanocortin-4 receptor mutations

Abstract: Transcriptional profiling was used to identify genes and pathways that responded to intracerebroventricular injection of melanocortin-4 receptor (MC4R) agonist [Nle(4), d-Phe(7)]-α-melanocyte stimulating hormone (NDP-MSH) in pigs homozygous for the missense mutation in the MC4R, D298 allele (n = 12), N298 allele (n = 12), or heterozygous (n = 12). Food intake (FI) was measured at 12 and 24 h after treatment. All pigs were killed at 24 h after treatment, and hypothalamus, liver, and back-fat tissue was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…The PRKAG3 AA animals also had less drip loss, which means higher water-holding capacity. Our results are consistent with previous reports in which the AA genotype pigs had Unfortunately, we did not have the backfat thickness records to test if the MC4R D298N polymorphism was associated with fat deposition traits in KNP x YS F2 animals, but it warrants the identification of the MC4R gene structure in KNP pigs to investigate the functional mechanisms of obesity-related phenotypes (Barb et al, 2010;Switonski et al, 2010). The CAST RsaI polymorphism was associated with moisture and crude protein levels (Table 4).…”
Section: Association Of Genotypes With the Phenotypessupporting
confidence: 91%
“…The PRKAG3 AA animals also had less drip loss, which means higher water-holding capacity. Our results are consistent with previous reports in which the AA genotype pigs had Unfortunately, we did not have the backfat thickness records to test if the MC4R D298N polymorphism was associated with fat deposition traits in KNP x YS F2 animals, but it warrants the identification of the MC4R gene structure in KNP pigs to investigate the functional mechanisms of obesity-related phenotypes (Barb et al, 2010;Switonski et al, 2010). The CAST RsaI polymorphism was associated with moisture and crude protein levels (Table 4).…”
Section: Association Of Genotypes With the Phenotypessupporting
confidence: 91%
“…Factors secreted by adipose tissue or "adipokines" continue to be discovered and are linked to important physiological roles (Ahima, 2006) including the innate immune response (Schäffler & Schöolmerich, 2010). In a number of recent experiments transcriptional profiling demonstrated that 5,000 to 8,000 adipose tissue genes were differentially expressed during central stimulation of the melanocortin 4 receptor (Barb et al, 2010a) and several conditions such as fasting (Lkhagvadorj et al, 2009) and feed restriction . In contrast, 300 to 1,800 genes were differentially expressed in livers in these three studies (Barb et al, 2010a;Lkhagvadorj et al, 2009Lkhagvadorj et al, , 2010.…”
Section: Adipose Tissue As An Endocrine Organmentioning
confidence: 99%
“…In a number of recent experiments transcriptional profiling demonstrated that 5,000 to 8,000 adipose tissue genes were differentially expressed during central stimulation of the melanocortin 4 receptor (Barb et al, 2010a) and several conditions such as fasting (Lkhagvadorj et al, 2009) and feed restriction . In contrast, 300 to 1,800 genes were differentially expressed in livers in these three studies (Barb et al, 2010a;Lkhagvadorj et al, 2009Lkhagvadorj et al, , 2010. This degree of differential gene expression in adipose depots reflects the potential influence of adipose tissue as a secretory organ on multiple systems in the body.…”
Section: Adipose Tissue As An Endocrine Organmentioning
confidence: 99%
See 2 more Smart Citations